Asymmetric synthesis of piperidine alkaloids - Thomson, A; Anthony Thomson (2012)
This thesis describes investigations into the total asymmetric synthesis of alkaloids from polysubstituted piperidines via iodolactonisation, resulting in the completion of an asymmetric synthesis of pseudodistomin D.